THE CATEGORY OF "DEVELOPMENT" IN THE CONTEXT OF PSYCHOLOGISTS' PROFESSIONAL IDENTITY - Nemash, Liliia (Personality and environmental issues, 2025)
The article deals with modern approaches to the study of the categories of personal identity, professional identity of psychologists of general secondary education institutions (or practical psychologists). Examples of the model of structural components of the formation of professional identity of future psychologists are given. The justification of the category "development" in terms of its antonym - "functioning" is given. The author defines and focuses on the understanding of the term "development" as an irreversible, directed, natural process that should take place in real time and subject to the fulfillment of all these components.The development of professional identity is a dynamic process that combines internal (self-reflection, motivation, values) and external (social, organizational) factors.The formed professional identity is an indicator of professional maturity and the basis for further self-realization.Goal setting, professional reflection, mentoring, and participation in the professional community are important conditions for development. Thus, the process of development of life and/or professional situation takes place, which generally affects the formation of the professional identity of psychologists of general secondary education institutions.